Las cadenas globales de producción en el marco de la disputa hegemónica mundial. Consideraciones para el desarrollo de América Latina - Carolina Teresita Lauxmann; Víctor Ramiro Fernández (Revista Iberoamericana de Estudios de Desarrollo)
In the article it is analysed the configuration and expansion of global production chains, as well as their current slowdown, based on a long term and systemic perspective. Specifically, it is studied these processes in the phase of the decline of the North American systemic cycle of accumulation and the emergence of a new dynamic centre of accumulation and potential hegemonic replacement: East Asia, led by China. In this disputed scenario, the work explores the possibilities and limitations that the engagement to global production chains represent for Latin America’s development. It is recognized that, so far, the insertion to the globalized production has not benefited the development of the countries of the region. However, it is identified the opportunity to modify this situation by the configuration of regional production networks, which will allow a more qualified insertion to global production chains.